Early reactions of EU-UK trade flows to Brexit - Eimear Flynn; Janez Kren; Martina Lawless (The Economic and Social Research Institute (ESRI), 2021)
This paper examines the early months of trade in goods between the United Kingdom and European Union in the aftermath of Brexit. Controlling for product-time and partner country effects across all European bilateral trade flows, we isolate the contribution of Brexit on trade in the first half of 2021 from other potential common drivers of trade flows including the COVID-19 pandemic. The results show sharp declines in trade from the UK to the EU, the majority of which can be attributed to a Brexit impact. We also document considerable variation across member states and sectors. The effect of Brexit is highly asymmetric, however, with reduction in trade from the EU to the UK approximately half the size of the fall from the UK to EU. This is likely explained by the more gradual implementation of customs checks by the UK. Reductions in trade are identified from the date of the referendum and no evidence of stockpiling in the months prior to Brexit is found on either side.
Keywords: F10; 330; Brexit; free trade agreements; customs checks